Responses to ostracism across adulthood - Hawkley, Louise C. (Oxford University Press, 2011)
Ostracism is ubiquitous across the lifespan. From social exclusion on the playground, to romantic rejection, to workplace expulsion, to social disregard for the aged, ostracism threatens a fundamental human need to belong that reflexively elicits social pain and sadness. Older adults may be particularly vulnerable to ostracism because of loss of network members and meaningful societal roles. On the other hand, socioemotional selectivity theory suggests that older adults may be less impacted by ostracism because of an age-related positivity bias. We examined these hypotheses in two independent studies, and tested mechanisms that may account for age differences in the affective experience of ostracism. A study of 18- to 86-year-old participants in the Time-Sharing Experiments for the Social Sciences program showed an age-related decrease in the impact of ostracism on needs satisfaction and negative affectivity. A study of 53- to 71-year-old participants in the Chicago Health, Aging, and Social Relations Study (CHASRS) showed that ostracism diminished positive affectivity in younger (<60 years) but not older adults. Age group differences in response to ostracism were consistent with the positivity bias hypothesis, were partly explained by age differences in the impact of physical pain, but were not explained by autonomic nervous system activity, computer experience, or intimate social loss or stressful life experiences.